The Association Between Impulsivity and Relapse in Patients With Alcohol Use Disorder: A Literature Review. (31st December 2020) - Sliedrecht, Wilco; Roozen, Hendrik G; Witkiewitz, Katie; de Waart, Ranne; Dom, Geert
Abstract: Aim: Impulsivity has been identified as a key relapse risk factor in patients with alcohol use disorder (AUD); however, the inherent characteristics of this relationship have been largely understudied. The heterogeneity of AUD and variation in impulsivity constructs require careful consideration to inform future work examining the relationship. This study sought to review empirical findings examining facets of impulsivity and AUD relapse. Methods: A systematic search strategy was employed to capture studies on impulsivity measures related to AUD relapse. Impulsivity measures were qualitatively organized in terms of 'trait impulsivity'—typically measured by self-report questionnaires—and 'behavioural impulsivity', i.e. 'motor impulsivity', 'impulsive choice' and 'reflection impulsivity, assessed with cognitive–behavioural tasks. Results: Seventeen peer-reviewed papers were identified. Relapse outcomes varied substantially in relation to impulsivity measures. Twelve papers included aspects of 'trait impulsivity', and nine studies included 'behavioural impulsivity' measures, from which five studies dealt with the 'impulsive choice' subcategory. The Barratt Impulsivity Scale was the self-report questionnaire that was most frequently used. Conclusions: All three included facets of impulsivity ('trait-, motor- and impulsive choice impulsivity') were associated with AUD relapse, but none seemed to be superior to another. This study confirmed that research on the relation between impulsivity and AUD relapse is relatively scarce. Future research and treatment options are proposed. Abstract : Short Summary : Impulsivity measures (categorized in terms of 'trait impulsivity' and 'behavioural impulsivity') are associated with alcohol use disorder (AUD) relapse. Research on this association is surprisingly scarce and suggests that specific facets of impulsivity are modestly associated with relapse. Targeting impulsivity in AUD treatment may reduce relapse risk.